POS1178 IDENTIFYING THE NEW DISORDER “IDIOPATHIC HYPOCRYOGLOBULINAEMIA” IN PATIENTS WITH PREVIOUSLY UNIDENTIFIED CLINICAL CONDITIONS - Roccatello, D.; Sciascia, S.; Naretto, C.; Barreca, A.; Solfietti, L.; Battaglia, L.; Viziello, L.; Fenoglio, R.; Rossi, D. (Annals of the rheumatic diseases, 2023)
BackgroundA considerable number of patients with high clinical suspicion for cryoglobulinaemic vasculitis either.show negative results for the detection of cryoglobulins or show only trace amounts which cannot.be characterized for composition.ObjectivesWe aimed at establishing whether the failure to detect or the detection of trace amounts of cryoglobulin with conventional methods either identifes a peculiar subset of low level cryoglobulinaemia (from now on hypocryoglobulinaemia) or represents a separate entity.MethodsUsing a modifed precipitation technique in hypo-ionic medium, we prospectively identified between 2008 and 2021 237 patients (median age 60.8 years [22–97], 137 females) having < 0.5% cryocrit and clinical suspicion of autoimmune disorder.ResultsOf these 237 patients, only 54 (22.7%) had a history of HCV infection. One hundred and sixty-nine out of 237 patients (71%) had an established underlying disease, while 68 patients (28.6%) (median age 62.9 years [29–93], 35 females) did not show either laboratory markers or clinical symptoms consonant with an underlying aetiology. These 68 cases with only trace amounts of cryoglobulins were defned as having a putatively idiopathic hypocryoglobulinaemia. Nineteen of these 68 patients (27.9%) had a history of HCV infection. Twentyfour patients out of 68 (35.3%) were positive for rheumatoid factor (RF), while 25 (36.7%) patients had signs of complement consumption (i.e., C4< 15 mg/dl and/or C3 < 80 mg/dl), and 36 (52.9%) had increased infammatory indexes. Seven patients only had arthralgia and constitutional symptoms while 61 out of 68 (89.7%) presented with at least one of the three cardinal signs of cryoglobulinaemic vasculitis including skin lesions, peripheral nerve involvement, and glomerulonephritis. Seventy-fve percent of the subjects had type III hypocryoglobulins. In patients with hypocryoglobulinaemia the histologic features of glomerulonephritis (also examined by electron microscopy) resembled those of mixed cryoglobulinaemia-associated glomerulonephritis.ConclusionIn conclusion, hypocryoglobulins are often polyclonal and are mainly unrelated to HCV infection. Patients who present high clinical suspicion for vasculitis, especially glomerulonephritis and yet test negative for cryoglobulinaemia detected by standard techniques, could require deeper investigation even in the absence of HCV infection, RF activity or signs of complement consumption.Reference[1]Meltzer, M. et al. Cryoglobulinemia, a clinical and laboratory study. Cryoglobulins with rheumatoid factor activity. Am. J. Med. 40, 837–856 (1966).Acknowledgements:NIL.Disclosure of InterestsNone Declared.